A Study Paper on Performance Degradation due to Excessive Garbage Collection in Java Based Applications using Profiler - Retna, Emi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Applications are becoming more complex, more larger and demand high quality. Application Server is the component on which most of the applications are hosted. It acts in the middle tier providing lot of functionalities like transaction management, caching ,persistence clustering etc. There are a variety of application servers to choose from like JBoss, Websphere, Tomcat etc, some are open source while others are proprietary. Quality parameters like performance, availability, scalability, maintainability, re-usability vary between different application servers. The application servers can be analyzed and monitored for performance using various tools and metrics. The quality parameters of an application server are affected by various factors such as memory leak, poor performing code, etc. It is necessary to evaluate the performance, to verify if the quality requirements are met. Software Engineering has several methodologies, metrics and calculations to evaluate the quality requirements. [1] discusses the various measurements and metrics that can be used to calculate the quality parameters.